Isthmic Agenesis and Thyroid Hemiagenesis Associated with Thyroiditis: A Case Report - Upadhyaya, Tirtha Lal; Parajuly, Shyam Sundar; Pangeni, Roshan (Journal of Diabetes and Endocrinology Association of Nepal, 2018)
Congenital thyroid anomalies are rare. Developmental anomalies may be in the form of unilateral or bilateral hypoplasia or agenesis of one or both lobes of thyroid with or without isthmic agenesis. Most of the times when they are detected incidentally already have associated thyroid diseases. We report a 36- year-old female presented with right thyroid hemiagenesis and isthmic agenesis associated with thyroiditis in left lobe of thyroid.Jour of Diab and Endo Assoc of Nepal 2018; 2 (1): 44-46